ANGIOGRAPHIC FEATURES OF PATIENTS WITH CORONARY ARTERY ECTASIA COMPARED WITH STENOTIC CORONARY ARTERY DISEASE - ULLAH, S; HUSSAIN, J (Biological and Clinical Sciences Research Journal, 2024)
Coronary artery ectasia (CAE) and coronary artery stenotic disease (CASD) represent distinct pathologies of the coronary arteries with remarkable clinical and angiographic features. Objectives: The study aims to find the angiographic features of patients with coronary artery ectasia compared with stenotic coronary artery disease. Methods: This retrospective study was conducted at Prime Teaching Hospital Peshawar from April 2023 to March 2024. Data were collected from 185 patients. Patients with a history of coronary artery bypass grafting or coronary intervention were excluded from the study. Baseline demographic and clinical characteristics, including age, gender, cardiovascular risk factors, hypertension, diabetes mellitus, hyperlipidemia, smoking history and presenting symptoms, were collected from electronic medical records. Results: Data were collected from 185 patients. The mean age of patients in the CAE group was 58.5 ± 8.3 years, and the CAD group was 63.2 ± 7.9 years. 55.6% of the male group was in CAE and 87% in the CAD group. Out of 185, 33% suffered from hypertension in CAE and 81.4% in the CAD group. The most common comorbidity was hyperlipidemia in the CAD group (72.9%). Stable angina was present in 44.4% of CAE and 60.7% of the CAD group. Unstable angina is most common in the CAD group (21.4%), and AMI was 10.7% and 11.1% in the CAD and CAE groups, respectively. Percutaneous Coronary Intervention (PCI) was most common in the CAD group, which was 75%. Conclusion: It is concluded that coronary artery ectasia (CAE) presents distinct angiographic and clinical features compared to stenotic coronary artery disease (CAD), including localised or diffuse dilatation of coronary arteries, a higher prevalence of silent ischemia, and lower utilisation of percutaneous coronary intervention (PCI).